Curriculum and legislation from the new curriculum guidelines for the physical education teachers - Maffei, Willer Soares [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP]; Filho, Dalton Müller Pessôa [UNESP]; Hirota, Vinícius Barroso (My University, 2017)
This research aimed to elucidate aspects of teacher education, which have been presented as the focus of the research in the period from 2005 to 2014, and how the new legislation for teacher education have affected the curriculum and courses of Physical Education. The arguments evidenced against the actual planning of legal rules for Physical Education in higher education level, as well as, argued against how the Curriculum grade has been developed, which had often approached the fragmentation of the formation. As alternatives, distinct points were proposed: changing legislation to return to the expanded grade, the need to enhance the knowledge about professional trends of formation and to build the Curriculum collectively. There is a need to review the administrative procedures and management of courses, leading to a collective construction of the Curriculum, without interferences of individual and local power interests over the major matter of the course.
Keywords: Legislation and curriculum; Physical education; Teacher education